Effect of pipe size on acetylene flame propagation in a closed straight pipe - Siti Zubaidah, Sulaiman; R. M., Kasmani; A., Mustafa; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; N. S., Noor Azmi; N. A. M., Harinder Khan (Penerbit UMP, 2017)
The understanding of flame propagation mechanism in a tube or pipe as a function of scale is needed to describe explosion severity. Acetylene is an explosively unstable gas and will lead to a violent explosion when ignited. To achieve the goal, an experimental study of premixed acetylene/air mixture at stoichiometry concentration was carried out in a closed straight pipe with different sizes of L/D (ratio of length to diameter) to examine the flame propagation mechanism. Pipes with L/D=40 and 51 were used. From the results, it was found that the smaller pipe with L/D=40 enhanced the explosion severity by a factor of 1.4 as compared to that of the bigger pipe with L/D=51. The compression effect at the end of the pipe plays an important role to attenuate the burning rate, leading to higher flame speeds and hence, increases the overpressure. In the case of L/D=40, the compression effect is more severe due to the larger expansion ratio, and this phenomenon would decrease the quenching effect and subsequently promote flame acceleration. Fast flame speeds of up to 600 m/s were measured in the smaller pipe during explosion development. From the results, it can be seen that the compression effect plays a major role in contributing to the higher burning rate and affects the overall explosion and flame speed development. Furthermore, the compression effect is more severe in the smaller pipe that leads to the detonation-like event. This mechanism and data are useful to design a safety device to minimise explosion severity.